Enhanced Protective Immunity Derived from Dendritic Cells with Phagocytosis of CD40 Ligand Transgene-engineered Apoptotic Tumor Cells via Increased Dendritic Cell Maturation. Issue 6 (November 2015) - Parameswaran, Sreejit; Khalil, Muhammad; Ahmed, Khawaja Ashfaque; Sharma, Rajendra K.; Xiang, Jim
Aims and Background: Dendritic cells (DCs) play a pivotal role in regulating CD8 + cytotoxic T-lymphocyte (CTL) responses. Currently, DC vaccines have been used in experimental animal models and clinical trials for evaluation of antitumor immunity. However, their efficacy is limited, warranting the improvement of DC-based cancer vaccines. CD40 ligand (CD40L) stimulates DC activation and maturation via CD40-CD40L interaction. We demonstrated that DCs that had phagocytized apoptotic tumor cells induced antitumor immunity. Methods: We generated CD40L-expressing (EG7-CD40L) and the control (EG7-Null) EG7 tumor cells by transfection of EG7 tumor cells with CD40L-expressing adenoviral vector AdVCD40L and the control vector AdVpLpA, respectively. We also generated DC vaccines (DC-EG7/CD40L and the control DC-EG7/Null) using DCs with phagocytosis of irradiated EG7-CD40L and EG7-Null tumor cells, and assessed their phenotype and immunogenicity by flow cytometry and animal studies in C57BL/6 mice. Results: We demonstrate that an irradiation of 9000-rad induced Annexin V-expressing cell apoptosis in most (~75%) tumor cells, and provide evidence for phagocytosis of apoptotic tumor cells by flow cytometry and confocal microscopy. The DC-EG7/CD40L cells showed higher expression of DC maturation markers (Ia b, CD40, CD80, and CD86) and peptide/major histocompatibility complex I than the control DC-EG7/Null cells. In addition, DC-EG7/CD40L vaccine stimulates more efficient (0.97%) tumor-specific CTL responses than DC-EG7/Null cells (0.31%). Furthermore, 80% (4/5) of mice immunized with DC-EG7/CD40L vaccine become tumor-free after EG7 tumor cell challenge, whereas DC-EG7/Null vaccine only delays immunized mouse death. Conclusions: Dendritic cells that have phagocytized CD40L-expressing apoptotic tumor cells appear to offer new strategies in DC cancer vaccines.